Essence of Strategy Is Now How to Change - Hunsaker, B. Tom (MIT Sloan Management Review, 2020)
In dynamic environments, understanding when and how to change is the essence of strategy. The most successful businesses today are those that identify when and how to change to improve strategic advantage. Tools that can help business leaders spot the opportunities and challenges that exist or are emerging in their company's specific context are now more relevant than the traditional strategy frameworks of the past.